Short-term memory and knowledge of L1 and L2 by Roma children of Cyprus - Kyuchukov, Hristo; Kyratji , Helen; Pelekani, Chryso (East European Journal of Psycholinguistics, 2024)
The study of short-term memory and language learning conducted with primary school Roma children in Cyprus aimed to determine how children who grow up in economically disadvantaged families learn their mother tongue (L1) Turkish and their second language (L2) Cypriot Greek. Two groups of children (20 children aged 8 and 20 children aged 10), a total of 40, were tested with the Picture short-term memory test, the Peabody vocabulary test, the sentence repetition test and the number repetition test. The study seeks to answer the research question: "How does the short-term memory test help Roma children to perform the tests in their L1 and L2?" The research findings were statistically analysed with SPSS and ANOVA and showed correlations between the independent factors of age group, gender, and testing language. The result showed that the children performed the tests much better in their mother tongue (L1). They need help learning some of the grammatical categories from the Greek language. The Processability Theory of Pienemann (1998) is examined. According to this theory, the production of linguistic structures is possible without any conscious or non-conscious attention because the locus of the attentive process is short-term memory. For the children to attain the necessary academic level of Greek, the teachers working with Roma children should receive training to develop children’s bilingualism when instructing children growing up in a multilingual environment such as Cypriot society. Disclosure Statement The authors reported no potential conflicts of interest. * Corresponding author: Hristo Kyuchukov, 0000-0002-1965-8908hristo.kyuchukov@us.edu.pl